2018
DOI: 10.1039/c8sm00925b
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface charge in the interaction of nanoparticles with model pulmonary surfactants

Abstract: Inhaled nanoparticles traveling through the airways are able to reach the respiratory zone of the lungs. In such an event, the incoming particles first come into contact with the liquid lining the alveolar epithelium, the pulmonary surfactant. The pulmonary surfactant is composed of lipids and proteins that are assembled into large vesicular structures. The question of the nature of the biophysicochemical interaction with the pulmonary surfactant is central to understand how the nanoparticles can cross the air… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(97 citation statements)
references
References 59 publications
(131 reference statements)
6
90
0
1
Order By: Relevance
“…Cholesterol which is responsible for less-ordered lipid structures in native surfactant is also absent in Curosurf 18 . Despite these differences, using cryo-TEM, we show that the lipid structures such as uni-or, multi-lamellar/vesicular structures with sizes ranging from a few tens of nanometers to about 2 µm are present in Curosurf 26,39 . These images are presented in S7.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Cholesterol which is responsible for less-ordered lipid structures in native surfactant is also absent in Curosurf 18 . Despite these differences, using cryo-TEM, we show that the lipid structures such as uni-or, multi-lamellar/vesicular structures with sizes ranging from a few tens of nanometers to about 2 µm are present in Curosurf 26,39 . These images are presented in S7.…”
Section: Resultsmentioning
confidence: 76%
“…The dispersions included neat silica nanoparticles at µg ml −1 , silica-Curosurf dispersions at X = 2 ( µg ml −1 , µg ml −1 ) and X = 20 ( µg ml −1 , µg ml −1 ), and neat Curosurf at µg ml −1 . We note that X = 2 exposure condition corresponds to the peak of light scattering intensity of dispersions signifying a mixing ratio where the interactions result in largest aggregates 26 . The condition X = 20 is closer to the estimated mixing ratio in the lungs 29 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Cryo-TEM images have also shown that the silica particles can be internalized in the vesicles, potentially reducing the number of effective bonds in the network formation. 47 In conclusion, it is found that above a threshold concentration, the pulmonary surfactant Curosurf® loaded with alumina particles undergoes a rheological transition from a liquid to a soft solid state. These variations in viscosity are important for alveoli whose function is based on the flow properties of the surfactant layer, as they could cause pulmonary diseases.…”
Section: Ii3 -Alumina Loaded Surfactant Showing a Soft Solid Behaviormentioning
confidence: 84%
“…1b). The dispersion stability was assessed using dynamic light scattering at pH 5 and 6.4 over extended periods of time (> months) 47 and the hydrodynamic diameters were found to be time independent at 7 = 64 nm, 60 nm and 34 nm, respectively. The surface charge density was determined using the polyelectrolyte assisted charge titration spectrometry at = +7.3e, +0.62e, and -0.31e nm -2 (Table I) Table I: List of nanoparticles and their characteristics.…”
Section: Iv1 -Materialsmentioning
confidence: 99%